Someone like you [compact disc, unabridged] : a novel - Kingsbury, Karen (Kingsbury, Karen. Baxter family., 2020)
Maddie Baxter West is shaken to the core when she finds out everything she believed about her life was a lie. Her parents had always planned to tell her the truth about her past: that she was adopted as an embryo. But somehow the right moment never happened. Then a total stranger confronts Maddie with the truth and tells her something else that rocks her world, Maddie had a sister she never knew about. Betrayed, angry, and confused, Maddie leaves her new job and fiancé, rejects her family's requests for forgiveness, and moves to Portland to find out who she really is. Dawson Gage's life was destroyed when London Quinn, his best friend and the only girl he ever loved, is killed. In the hospital waiting room, London's mother reveals that London might have had a sibling. The frozen embryo she and her husband donated decades ago. When Dawson finds Maddie and brings her to Portland, the Quinns--her biological parents--welcome her into their lives and hearts. Maddie is comforted by the Quinns' love and intrigued by their memories of London, who was so much like her. Is this the family and the life she was really meant to have? Now it will take the love of Dawson Gage to help Maddie know who she is...and to help her find her way home.